THE ASTROMETRIC AND PHOTOMETRIC RESULTS OF DIGITIZED PLATES ON EPSON EXPRESSION 10000XL SCANNER WITH DIFFERENT RESOLUTIONS - Yuldoshev, Q.; Andruk, V.; Muminov, M, (Одеські астрономічні публікації, 2019)
This work was done to assess the accuracy of the plate processing method and to study in detail the Epson Expression 10000XL scanner, which is used to digitize the FON-Kitab astronomical plates from the photographic archive collection of the Ulugh Beg Astronomical Institute (UBAI) of the Uzbekistan Academy of Sciences. The glass archive of the UBAI has about 15 thousand photographic plates with images of various space objects. To process the plates the specially developed software in the LINUX/MIDAS/ROMAFOT was used. From comparing the results of processing digitized files with grayscale 8 and 16 bits, an assessment of the accuracy of the developed method for determining rectangular coordinates and photometry was made. The Epson Expression 10000XL flatbed scanner together with developed software can be used to digitize and process the astronegatives and obtain characteristics of objects (high, medium and moderate brightness) with an internal accuracy better than 0.05ʺ and 0.015 m for equatorial coordinates and B-magnitudes, respectively. To assess the repeatability of astrometric and photometric errors of the scanner, six consecutive scans of one plate with 600, 900, 1200, 1500, 1800, 2100, 2400 and 2540 dpi spatial separations were processed. The average accuracies of measurements were σ αδ =0.07ʺ for the equatorial coordinates and σ m =0.13 m for B-magnitudes. The results of the xperiments showed that a scan mode with a spatial resolution of 1200 dpi is the best option for plate digitization. Higher resolution scanning modes require a significant increase of digitizing and processing times of a plate, but they do not affect on an accuracy of the obtained results.